WOMEN AS A MANDATE FOR GLORY IN THE DYNAMICS OF CIVILIZATION - Agahirber, Agahirber; Sunarso, Sunarso; Syahrul, Syahrul (International Journal of Social Service and Research, 2025)
This paper aims to explore the relationship between "women and civilization" by highlighting the need to eliminate misogynistic attitudes and views that still influence many aspects of society. The main focus of this study is to distinguish whether women are considered as productive entities who contribute significantly in various fields or are only seen as having a reproductive function. This paper uses a qualitative method with a literature study approach to explore and analyze data in depth based on relevant literature. By analyzing the role of women in historical and modern contexts, this paper assesses the consequences of such attitudes, referencing tragedies such as the Nanjing atrocity in 1937, which highlights an episode of cruelty against women in situations of war and conflict, and how this violence reflects and reinforces such attitudes. The paper also discusses how internal factors, including women's own perceptions of their roles, can hinder their progress. The significance of Pancasila as an answer lies in its ability to become a bridge between traditional values and the demands of modernity in achieving gender equality in Indonesia. This study could examine the effectiveness of contemporary feminist movements in navigating the challenges posed by globalization, particularly in balancing their productive and reproductive roles. Lastly, comparative studies across different cultures could provide deeper insights into how various societies successfully implement strategies to overcome patriarchal norms and promote gender equality, ultimately enriching the discourse on women as "master chefs" of civilization.